Calcium supplementation on lowering blood pressure in pregnant women with hypertension: A meta-analysis - Zakiah Radjulaeni; Suhartono Suhartono; Mardiyono Mardiyono (Alma Ata University Press, 2023)
Background: Hypertension in pregnancy causes 10% of pregnancy disorders worldwide which results in maternal morbidity and mortality of 9-26% and the incidence of premature births as much as 15% worldwide. From the results of previous meta-analysis, there is a relationship between calcium intake and the incidence of preeclampsia by consuming 1500-2000mg calcium during pregnancy, it is necessary to add calcium supplements to pregnant women because not all calcium intake in pregnant women from food is sufficient to meet calcium needs. Objectives: Analyzing research studies on the effect of calcium on systolic blood pressure in pregnant women with hypertension in pregnancy, Analyzing research studies on the effect of calcium on diastolic blood pressure in pregnant women with hypertension in pregnancy. Methods: Meta analysis by searching 24 research studies from 5 databases (Pubmed, Science Direct, Google Schoolar, Elsevier, and Proquest) using Randomized Control Trial (RCT), Experimental, and Cohort, published in 2013-2020. Results: the results of the analysis of 5 studies involving 945 selected pregnant women with an average use of moderate doses (500 mg / day during the study) were divided into 2 groups. Providing calcium intervention since 20 weeks of gestation showed that calcium supplementation had a decreasing impact on maternal blood pressure in pregnancy. Analysis showed a difference in blood pressure in mothers with hypertension in pregnancy compared to mothers who did not consume calcium. Conclusions: The use of calcium supplements during pregnancy can reduce blood pressure and prevent preeclampsia. The recommended dose is 500 mg/day from 20 weeks of gestation with mothers at risk of preeclampsia. Health workers need to ensure that pregnant women comply with the calcium consumption rules given so that the management recommendations can be carried out properly